Analisis Pemasaran Ikan Segar Laut Di Kecamatan Padang Utara Kota Padang Dengan Pendekatan SWOT - Ira Desmiati; Lolitha Uthary; Reffi Aryzegovina; Dian Eka Putra (JURNAL PUNDI, 2022)
Fishery production in Padang City is dominated by catch fisheries. The catch of fish from year to year continues to increase. The purpose of this research is to study the marketing of fresh marine fish in Padang Utara District, Padang City with the SWOT method approach so that it can help traders in facing market competition and increasing sales in the future. The results showed that the more appropriate strategy to be used in determining the business development strategy of fresh sea fish traders in North Padang District, Padang City was in quadrant III, which means that it supports the Turn Around Strategy (reverse strategy) which is to achieve opportunities for fresh sea traders in the District. North Padang is very big, but on the other hand it faces some internal constraints/weaknesses. The focus of this strategy is to minimize the internal problems of fresh sea traders in North Padang District so that they can improve a better development strategy